2012
DOI: 10.1007/s12011-012-9337-5
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Smoking Status of Family Members and Concentrations of Toxic Trace Elements in the Hair of Children

Abstract: Hair analysis is a promising tool for routine clinical screening and diagnosis of heavy metal exposure and essential trace element status in the human body. Systemic intoxications have been identified by anomalously high values of toxins in hair samples. The aim of the present study is to evaluate the relationship between smoking habit of the family members and the levels of toxic and nontoxic trace elements in hair samples of children. The randomized cross-sectional controlled study comprised of 95 children (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…Indeed, multivariate models evidenced that several elements increased significantly in urine of ETS exposed children, when cohabitants are used to smoke at home when they are in. In particular, this association occurred for Li, Ti, V, Co, Ga, Sr. Other studies reported a significant positive correlation between the intensity of ETS exposure in general population and increased levels of some tobacco-related elements in different biological matrices (hair, blood, urine) (Richter et al, 2009;Serdar et al, 2012;Viroonudomphol et al, 2016). Each of these studies, however, reported significant increases for different elements; Serdar et al (2012), for example, found that Pb, Cd, Cu, Ni, and Sb levels in children's hair were positively correlated with the number of smokers and the frequency of smoking at home.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, multivariate models evidenced that several elements increased significantly in urine of ETS exposed children, when cohabitants are used to smoke at home when they are in. In particular, this association occurred for Li, Ti, V, Co, Ga, Sr. Other studies reported a significant positive correlation between the intensity of ETS exposure in general population and increased levels of some tobacco-related elements in different biological matrices (hair, blood, urine) (Richter et al, 2009;Serdar et al, 2012;Viroonudomphol et al, 2016). Each of these studies, however, reported significant increases for different elements; Serdar et al (2012), for example, found that Pb, Cd, Cu, Ni, and Sb levels in children's hair were positively correlated with the number of smokers and the frequency of smoking at home.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, this association occurred for Li, Ti, V, Co, Ga, Sr. Other studies reported a significant positive correlation between the intensity of ETS exposure in general population and increased levels of some tobacco-related elements in different biological matrices (hair, blood, urine) (Richter et al, 2009;Serdar et al, 2012;Viroonudomphol et al, 2016). Each of these studies, however, reported significant increases for different elements; Serdar et al (2012), for example, found that Pb, Cd, Cu, Ni, and Sb levels in children's hair were positively correlated with the number of smokers and the frequency of smoking at home. Richter et al (2009), instead, evidenced that the urinary concentrations of Cd, Pb, Sb, Ba, Be, Cs, Co, Molybdenum (Mo), Pt, Tl, Tungsten (W) of subjects aged from 6 to N65 years old increased in a similar fashion as theoretical tobacco smoke exposure increase, from unexposed to smokers.…”
Section: Discussionmentioning
confidence: 97%
“…They naturally accumulate relatively high levels of elements such as Cu, Pb, Ni, Cd or Fe. This may be the answer why subjects who declared to be smokers had higher amounts of Cu in hair than non-smokers (Afridi et al, 2011;Serdar et al 2012). Surprisingly, the content of Pb was at the similar level in hair of non-smokers and smokers.…”
Section: Male Femalementioning
confidence: 95%
“…Copper is an important element nutritionally and in terms of toxicity (23). The copper is the basic component of hair, skin flexible parts, bone and some internal organs as well as being important in terms of bodily functions.…”
Section: Resultsmentioning
confidence: 99%